2015
DOI: 10.21608/ejnf.2015.104349
|View full text |Cite
|
Sign up to set email alerts
|

Use of Moringa Leaves (Moringa Oleifera) in Fattening Lambs Rations

Abstract: he effect of moringa leaves (Moringa oleifera) on fattening lambs, digestibility, feeding values, feed conversion, growth performance and economical evaluation were studied. The moringa leaves was included at a rate of 0, 7.5, 15 and 30% of the tested rations replacing soybean meal forming four dietary treatments. The control ration consisted of 75% concentrate feed mixture + 25% wheat straw. Twenty lambs with average live body weight 45 ± 1.0 kg at 10 months of age were used for 90 days feeding period. Five a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…In addition, a Moringa diet increased the average daily weight gain and milk yield of Najdi ewes compared to those fed alfalfa diets (Babiker et al, 2016;Babiker et al, 2017) (Figure 3). Lambs fed 75% and 100% Moringa foliage in a rice straw diet exhibited a positive growth performance, good carcass traits, and reduced subcutaneous fat (Sultana et al, 2017), similar to results obtained by Allam et al (2015), who found that rations containing Moringa leaves improved the feed conversion and growth performance. Lambs fed 0, 25, and 50 g/kg DM M. oleifera root bark exhibited improvements in feed efficiency and body N retention, ultimately increasing the mean daily gain of these lambs (Soltan et al, 2018).…”
Section: Use In Sheep Feedingsupporting
confidence: 84%
“…In addition, a Moringa diet increased the average daily weight gain and milk yield of Najdi ewes compared to those fed alfalfa diets (Babiker et al, 2016;Babiker et al, 2017) (Figure 3). Lambs fed 75% and 100% Moringa foliage in a rice straw diet exhibited a positive growth performance, good carcass traits, and reduced subcutaneous fat (Sultana et al, 2017), similar to results obtained by Allam et al (2015), who found that rations containing Moringa leaves improved the feed conversion and growth performance. Lambs fed 0, 25, and 50 g/kg DM M. oleifera root bark exhibited improvements in feed efficiency and body N retention, ultimately increasing the mean daily gain of these lambs (Soltan et al, 2018).…”
Section: Use In Sheep Feedingsupporting
confidence: 84%
“…However, both moringa and cassava leaves are well-known as great protein sources. The protein content of moringa leaves varied from 21.8-40.8 % DM [23][24][25], while cassava leaves were about 17.8 -37.4% DM [26,27]. It could be presumed that the nutritional value of animal diets was also influenced by the additional rich-nutrient components, such as milk and soybean.…”
Section: Resultsmentioning
confidence: 99%
“…Não houve efeito significativo da Moringa sobre a massa corporal dos animais controle, divergindo dos resultados de Allam et al (2015) que obtiveram aumento no ganho de massa corporal, na ordem de 15 e 7,5% para ovelhas de 10 meses alimentadas com extrato de folhas de Moringa. Segundo os autores a melhora no ganho de massa em animais não-obesos poderia ser atribuída a baixa quantidade de extrato de Moringa fornecido, uma vez que o excesso de extrato pode indicar aumento de proteínas brutas na alimentação, pois são insolúveis em água (ALLAM et al, 2015). Nossos resultados convergem com os obtidos por Almatrafi et al (2017), no qual cobaias, não apresentaram aumento de massa corporal, independente do grupo experimental ou da quantidade de Moringa ingerida durante seis semanas.…”
Section: Icc (%)unclassified